Pengaruh Latihan Box Jump dan Depth Jump Sprint Terhadap Hasil Shooting Sepak Bola Ektrakurikuler SMP PGRI Kundi - Wendy Arizona; Mutiara Fajar; Hikmah Lestari (Journal on Education, 2023)
The problem with this research is the lack of increased results from extracurricular football shooting of kundi pgri middle school. The aim of this study is to understand the impact of box jump and sprinting sprinting against kundi junior high football shooting. In this study are two free variables (x) and 1 variable (y). Research methods use the quantitative method or field experiment. The population and sample of this study are 20 students and data collection techniques using the pre-forgiveness tretforgiveness test. The instrument used is the ball, stopwatch, goal, Numbers, ropes, with the analyst technique using the t-test based on the research data made on extra-seventh pgri kundi junior high school student, box jump exercises got a t-count count of = 4.602 centimeters = 1.833. On the other hand, the jump sprints with a t-count of 4.609, the chart is 1,833. And to find out which of the two most influential exercises is correct from the average value of pretest and posttest in experiment group 1 is 6.80 and 10.80. Whereas the average value of pretest and posttest groups of experiment 2 was 5.90 and 8.30. Thus there was an increase of 4.00 in experiment group 1 while the increase in experiment group 2 was 2.40. It is known that a percentage increase is 100%.